Man/Cel5B, a Bifunctional Enzyme Having the Highest Mannanase Activity in the Hyperthermic Environment - Sadaqat, Beenish; Sha, Chong; Rupani, Parveen Fatemeh; Wang, Hongcheng; Zuo, Wanbing; Shao, Weilan (Frontiers in Bioengineering and Biotechnology, 2021)
Thermotoga maritima (Tma) contains genes encoding various hyperthermophilic enzymes with great potential for industrial applications. The gene TM1752 in Tma genome has been annotated as cellulase gene encoding protein Cel5B. In this work, the gene TM1752 was cloned and expressed in Escherichia coli, and the recombinant enzyme was purified and characterized. Interestingly, the purified enzyme exhibited specific activities of 416 and 215 U/mg on substrates galactomannan and carboxy methyl cellulose, which is the highest among thermophilic mannanases. However, the putative enzyme did not show sequence homology with any of the previously reported mannanases; therefore, the enzyme Cel5B was identified as bifunctional mannanase and cellulase and renamed as Man/Cel5B. Man/Cel5B exhibited maximum activity at 85 °C and pH 5.5. This enzyme retained more than 50% activity after 5 h of incubation at 85 °C, and retained up to 80% activity after incubated for 1 h at pH 5-8. The Km and Vmax of Man/Cel5B were observed to be 4.5 mg/mL galactomannan and 769 U/mg, respectively. Thin layer chromatography depicted that locust bean gum could be efficiently degraded to mannobiose, mannotriose and mannooligosaccharides by Man/Cel5B. These characteristics suggest that Man/Cel5B has attractive applications for future food, feed and biofuel industries.